2023
DOI: 10.1021/acs.energyfuels.3c01430
|View full text |Cite
|
Sign up to set email alerts
|

Coreflood Testing of Gas-Blocking Agents: Selectivity in High-Heterogeneity Reservoirs and Efficiency in Low-Temperature Conditions

Abstract: Gas breakthrough is becoming an increasingly common problem, with a growing number of gas-and-oil fields being developed. Gas-and-oil fields are usually characterized by a complex geological structure, high reservoir heterogeneity, low net-pay thickness, and large gas cap, which lead to gas breakthrough, especially in horizontal production wells. Chemical gas-blocking methods lately have gained more scientific interest and are becoming more applicable in the fields, the reason being the potential for adjusting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…Experimental and field studies confirm the results of several research groups on the advantages of FGC over polymer foams, foams and hydrogels for gas isolation [11,22,34]. It should be noted that the use of self-generating FGC with the subsequent injection of hydrogel for gas isolation is a new type of technology for gas flow restriction in oil wells.…”
Section: A Comparison Of the Results Of This Study With Previously Pu...supporting
confidence: 73%
See 2 more Smart Citations
“…Experimental and field studies confirm the results of several research groups on the advantages of FGC over polymer foams, foams and hydrogels for gas isolation [11,22,34]. It should be noted that the use of self-generating FGC with the subsequent injection of hydrogel for gas isolation is a new type of technology for gas flow restriction in oil wells.…”
Section: A Comparison Of the Results Of This Study With Previously Pu...supporting
confidence: 73%
“…The dynamic definitions of the modulus of elasticity and the modulus of viscosity are provided in Figure 6, which shows that the region of viscoelastic behavior is constant over a large range of applied stresses. Consider that the gas shutoff properties of FGC were determined in previous studies [34], in which it was shown that the foam gel efficiency is many times higher than that of the foam polymer and hydrogel. Therefore, in this study, the water shutoff properties of FGC were clarified, and filtration experiments were conducted in the porous media of Consider that the gas shutoff properties of FGC were determined in previous studies [34], in which it was shown that the foam gel efficiency is many times higher than that of the foam polymer and hydrogel.…”
Section: Tested Compositionmentioning
confidence: 99%
See 1 more Smart Citation